PENGARUH PENERAPAN METODE PEMBELAJARAN QUIZ TEAM TERHADAP MOTIVASI BELAJAR MATA PELAJARAN PENDIDIKAN PANCASILA PADA SISWA KELAS IV SD NEGERI KALIREJO 02 KECAMATAN UNGARAN TIMUR KABUPATEN SEMARANG - Pujiati, Ayum; Widayati, Sri; Wijayanti, Atrianing Yessi (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This research aims to determine whether or not there is an influence of the application of the Quiz Team learning method on motivation to learn Pancasila Education subjects in students Class IV of Kalirejo 02 State Elementary School. This research uses a quantitative approach with the Quasi Experiment method. This research aims to develop a local stories book in Indonesian language subjects for grade 1 elementary school students in Singorojo District, Kendal Regency. This research also aims to determine the validity and practicality of the local stories book which was developed according to students' needs. This research uses a development model according to Sugiyono which includes potential and problems, data collection, product design, design validation, design improvement, product testing, and product revision. The data analysis techniques used are quantitative and qualitative, the variables studied include the validity of the local stories book which was developed through validation by expert experts and practicality based on student questionnaire responses. Based on the research results, it was found that (1) the local stories book validity test by material experts obtained an overall score of 87; (2) media expert aspects of book size, book cover design, and book content design received an overall score of 92; (3) and the practicality test based on the student response questionnaire obtained a score of 88.8. Thus, it is hoped that this research can make a contribution to the field of education and provide solutions that can be used by teachers in facing future learning challenges.